DNA methylation and hydroxymethylation analyses of the active LINE-1 subfamilies in mice. Issue 1 (December 2017) - Murata, Yui; Bundo, Miki; Ueda, Junko; Kubota-Sakashita, Mie; Kasai, Kiyoto; Kato, Tadafumi; Iwamoto, Kazuya
Abstract Retrotransposon long interspersed nuclear element-1 (LINE-1) occupies a large proportion of the mammalian genome, comprising approximately 100, 000 genomic copies in mice. Epigenetic status of the 5′ untranslated region (5′-UTR) of LINE-1 is critical for its promoter activity. DNA methylation levels in the 5′-UTR of human active LINE-1 subfamily can be measured by well-established methods, such as a pyrosequencing-based assay. However, because of the considerable sequence and structural diversity in LINE-1 among species, methods for such assays should be adapted for the species of interest. Here we developed pyrosequencing-based assays to examine methylcytosine (mC) and hydroxymethylcytosine (hmC) levels of the three active LINE-1 subfamilies in mice (TfI, A, and GfII). Using these assays, we quantified mC and hmC levels in four brain regions and four nonbrain tissues including tail, heart, testis, and ovary. We observed tissue- and subfamily-specific mC and hmC differences. We also found that mC levels were strongly correlated among different brain regions, but mC levels of the testis showed a poor correlation with those of other tissues. Interestingly, mC levels in the A and GfII subfamilies were highly correlated, possibly reflecting their close evolutionary relationship. Our assays will be useful for exploring the epigenetic regulation of the active LINE-1 subfamilies in mice.